The Influence Of Sports Facility Management And Teacher Services On The Effectiveness Of Physical Education - Donny Setiawan; Antonius Tri Wibowo (Journal Management of Sport, 2023)
This study aimed to assess the level of management of sports facilities and teacher services in relation to the effectiveness of physical education in high schools. In this study, the researchers employed a descriptive survey research method. The participants of this study consisted of physical education instructors and eleventh-grade students from public high schools in Banyuwangi Regency, comprising a total of 3500 students. A random sampling procedure was employed, resulting in a sample size of 95 pupils. Two commonly used methods for collecting data are questionnaires and documentation. The author conducted data analysis using various statistical tests, including the correlation coefficient test, the coefficient of determination, the t test, and the F test. Based on the findings of the study, it has been determined that: 1) The school's facility management is deemed adequate; 2) The services rendered by teachers are deemed satisfactory. There is sufficient quality in both facility management and instructor services.